Using genomic data for selecting the treatment of lymphoma patients. Issue 4 (July 2019) - Batlevi, Connie Lee; Shah, Gunjan; Forlenza, Christopher; Intlekofer, Andrew
Abstract : Purpose of review: Genomic profiling platforms provide unprecedented genetic information of lymphoma biology, yet information has yet to be readily integrated into clinical medicine. This review summarizes the important concepts of utilizing genomics to aide disease management. Recent findings: A wide range of clinical grade genetic sequencing platforms are available, therefore the selection of sequencing platform should ideally be based on biological and clinical questions, as well as the strength and weaknesses of individual platform. Different evidence-based guidelines exist to aide clinical judgment; however, few have well curated, easy to search platforms. Using one guideline proposed by several regulatory groups, our review summarizes genetic alterations with diagnostic, prognostic and therapeutic potential in the major subtypes of lymphoma. Summary: A comprehensive database of genetic alterations that contribute to clinical care in lymphoma is needed. Ideally, a database which accounts for single and pathway-based genetic alterations may be developed to guide development and interventions for management of lymphoma.